Public Services for the Tourism Sector During the Covid-19 Pandemic In Bukittinggi City - Ihsan Hasbi Alfaruqi; M Fachri Adnan (Program Pascasarjana Universitas Negeri Makassar, 2022)
This study aims to analyze the implementation of public services during the Covid-19 pandemic at the Bukittinggi City Tourism, Youth and Sports Office, analyze the quality of public services that were hindered by the Covid-19 pandemic at the Bukittinggi City Tourism, Youth and Sports Office and analyze the factors that influence public services during the Covid-19 pandemic at the Bukittinggi City Tourism, Youth and Sports Office. This type of research is qualitative with a descriptive method and was carried out at the Office of Tourism, Youth, and Sports of Bukittinggi City and the technique used in testing the validity of the data is by using triangulation techniques. The results of this study are 1. The implementation of public services during the Covid-19 pandemic at the Tourism, Youth, and Sports Office of Bukittinggi City, namely productivity, service quality, responsiveness, responsibility, and accountability, 2. The quality of public services that are hindered by the Covid-19 pandemic 19 at the Tourism, Youth, and Sports Office of the City of Bukittinggi, namely the delivery of service information through information bulletin boards and pamphlets, improving the online service delivery system, and increasing the competence of service implementers. 3. The factors that affect public services during the Covid-19 pandemic at the Tourism, Youth and Sports Office of Bukittinggi City are the right policy response in the tourism sector, careful planning, sustainable cooperation, quality MSME products, and socializing return to the tourism sector through the media.